BIOLOGY, HABITAT AND CONSERVATION OF INDIAN ROCK PYTHON-A BRIEF REVIEW - M. E. Babar; M. S. Mughal; T. Hussain; M. M. Javed; S. Sherzada; S. A. Khanand A. Ali (Journal of Animal and Plant Sciences, 2019)
The earth ecosystem is facing instability in the present era due to unbridled devastating human activities across the globe. as a result  we are losing species  globally day by day. Indian Rock Python (Python molurus molurus) commonly recognized and pronounced as Indian Python, is considered as one among the list of larger size non-venomous snakes  which is widely distributed all through Indian subcontinent particularly in Indus valley as well as Punjab region of Pakistan reaching up to Kashmir. It has been included in near threatened class in the IUCN Red List of species (IUCN, 1996). Jurgen et al., 1988). It dwells in a  broad range of living conditions ranging from dry to rocky and from rocky to scrubs as well as moist jungles (Murphy and Henderson, 1997; De Vosjoli, 1991; Jurgen et al., 1988),  the main evidence for its common name i.e. Indian Rock Python (Avadhani, 2005). As far as Pakistan is concerned, most of the python rich or inhabited localities are being preferably transformed into agricultural lands which are resultantly restricting it to the Southern Sindh, Indus Valley and its tributaries or the riparian zone (Masroor, 2012). But as a matter of fact, even in these areas it is noted to be diminishing at fast rate (Azam et al., 2007). Only a few pythons have been reported in district Sanghar in Sindh, Deva Vatala National Park, Azad Jammu & Kashmir (Goursi et al., 2012) , District  Narowal (Shakargarh), and Gujarat are on the verge of extinction as reported by Khan, 2006.
Keywords: Python molurus molurus; IUCN Red List; Deva Vatala National Park; Indus Valley.